The relationship of homeless, autonomy and vulnerability: a challenge for bioethics - Soto-Méndez, Carolina (Acta Bioethica, 2019)
The purpose of this article is to identify the relationships between vulnerability and autonomy that academic literature has developed in relation to homeless. For the fulfillment of the objective, a bibliographic search was developed in different databases under the criteria of homeless, autonomy, decision making, vulnerability, bioethics. As a conclusion, it is clear that the mental problems that this population group can present demonstrate the difficulties that exist to resolve the false bioethical dichotomy that exists between autonomy and vulnerability. A new task for bioethics is identified, such as overcoming the presented dichotomy that can provide substantial elements that help to overcome the difficulties that arise for the attention of homeless.